Epidemiological Features of Human Cases After Bites/Scratches From Rabies-suspected Animals in Zenica-Doboj Canton, Bosnia and Herzegovina - Uzunović, Selma (J Prev Med Public Health, 2019)
OBJECTIVES: To determine the epidemiological features of patients and animals after bites/scratches from rabies-suspected animals in Zenica-Doboj Canton, Bosnia and Herzegovina. METHODS: Data from all patients (and the causative animals) admitted to the Antirabies Service of the Institute for Health and Food Safety Zenica in the 2009-2017 period were analyzed, including age, sex, anatomical site of the bite/scratch, animal type (stray/owned/wildlife), veterinary observations of the animal, and whether antirabies post-exposure prophylaxis (PEP) was indicated and/or administered. RESULTS: In total, 1716 patients were admitted. Bites/scratches were most frequently recorded during April and May (n=181, 10.5% and n=163, 9.5%, respectively). The persons admitted were mostly from the Zenica municipality (n=1278, 74.5%; incidence: 11.55/ 1000), which is 66.6% urbanized. Males were more frequently represented (n=1089, 63.6%). The patients were mostly 50-64 and 25-49 years of age (n=425, 24.7% and n=390, 22.7%, respectively). Dog bites were the most common cause (n=1634, 95.1%, of which n=1258, 77.0% were caused by stray dogs). PEP was indicated for 997 (58.1%) patients. Only 340 (19.9%) animals underwent veterinary observations (3.1% of stray and 76.1% of owned animals). The largest number of injuries were presented at lower extremities, 1044 (60.8%) cases. CONCLUSIONS: Zenica-Doboj Canton is a rabies-free region. Due to the high rate of stray animals not undergoing veterinary observations, the non-existence of a unique dog registry, and the consequent lack of information about stray animals in terms of number, vaccination, neutering, and euthanasia, there is an urgent need for improving the prevention and control of rabies within the One Health framework.